Refecting on the Science of Climate Tipping Points to Inform and Assist Policy Making and Address the Risks they Pose to Society - Stocker, Thomas F.; Jones, Richard G.; Hegglin, Michaela I.; Lenton, Timothy M.; Hegerl, Gabriele C.; Seneviratne, Sonia I.; id_orcid:0 000-0001-9528-2917; van der Wel, Narelle; Wood, Robert A. (Springer, 2024)
There is a diverging perception of climate tipping points, abrupt changes and surprises in the scientific community and the public. While such dynamics have been observed in the past, e.g., frequent reductions of the Atlantic meridional overturning circulation during the last ice age, or ice sheet collapses, tipping points might also be a possibility in an anthropogenically perturbed climate. In this context, high impact-low likelihood events, both in the physical realm as well as in ecosystems, will be potentially dangerous. Here we argue that a formalized assessment of the state of science is needed in order to establish a consensus on this issue and to reconcile diverging views. This has been the approach taken by the Intergovernmental Panel on Climate Change (IPCC). Since 1990, the IPCC has consistently generated robust consensus on several complex issues, ranging from the detection and attribution of climate change, the global carbon budget and climate sensitivity, to the projection of extreme events and their impact. Here, we suggest that a scientific assessment on tipping points, conducted collaboratively by the IPCC and the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services, would represent an ambitious yet necessary goal to be accomplished within the next decade. ISSN:0169-3298 ISSN:1573-0956